TRANSITION FROM PASSIVE TO ACTIVE RIFTING: RELATIVE IMPORTANCE OF ASTHENOSPHERIC DOMING AND PASSIVE EXTENSION OF THE LITHOSPHERE - Huismans R.S.; Cloetingh S.; Podladchikov Y.Y. (My University, 2001)
We present quantitative modeling results of the dynamic interplay of passive extension and active convective thinning of the mantle lithosphere beneath intracontinental rift zones investigating the relative importance of thermal buoyancy forces associated with asthenospheric doming and far-field intraplate stresses on the style of rifting. To this aim we employ a twodimensional numerical code based on a finite element method formulation for nonlinear temperature dependent viscoelastoplastic rheology. Brittle behavior is modeled using Mohr-Coulomb plasticity. The models support a scenario in which passive stretching leads to an unstable lithospheric configuration. Thermal buoyancy related to this asthenospheric doming subsequently drives active upwelling in a lithosphere scale convection cell. In the late synrift to early postrift the lithospheric horizontal stresses caused by the active asthenospheric upwelling may start to compete with the far-field intraplate stresses. At this stage the domal forces may dominate and even drive the system causing a change from passive to active rifting mode. If this transition occurs, the model predicts (1) drastic increase of subcrustal thinning beneath the rift zone, (2) lower crustal flow towards the rift flanks, (3) middle crustal flow towards the rift center, (4) the coeval occurrence of tensional stresses within and compressive stresses around the upwelling region, and (5) possible surface uplift. Late postrift thermal cooling removes the thermal buoyancy forces. At this stage the far-field forces dominate the stress state again and the lithosphere becomes more sensitive to small changes in the intraplate stresses. The model results may explain several key observations that are characteristic of a large number of intracontinental rift basins. These features include differential thinning of extending lithosphere, the discrepancy between fault-related extension and crustal thinning, late (end of synrift to early postrift) mantle related volcanism, surface domal uplift succeeding rifting, and rift flanks uplift associated with extension of a weak lithosphere.